Comentario bibliográfico.L. Millones Figueroa; D. Ledesma (Eds.), El saber de los jesuitas, historias naturales y el Nuevo Mundo, Madrid, iberoamericana , 2005 - Justo, María de la Soledad (2008)
Fil: Justo, María de la Soledad. Universidad de Buenos Aires; Argentina